2019
DOI: 10.17524/repec.v13i4.2480
|View full text |Cite
|
Sign up to set email alerts
|

Uma abordagem para avaliação da qualidade do processo de pesquisa em Contabilidade

Abstract: Objetivo: analisar o processo de construção da produção científica em Contabilidade ao associar atributos de qualidade de uma boa pesquisa descritos na literatura com aqueles percebidos nas práticas de pesquisadores da área. Método: foi utilizada a Técnica Delphi Modificada, em duas rodadas, com questionários online e acesso personalizado. O painel foi composto por 41 docentes de 19 Programas de Pós-Graduação em Contabilidade brasileiros. Foi elaborada uma matriz de orientação com 53 atributos/relações v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Regarding the first axis, regarding the form, Murcia and Borba (2008) proposed an evaluation methodology for the scientific journals of accounting and auditing published in English and made available in the CAPES Periodicals Portal. With regard to the evaluation criteria established by CAPES of national and international journals in the areas of Administration and Accounting and Tourism, Oliveira and Martins (2014) emphasize that they are based, mainly, on the evaluation of the form of these journals, without emphasis on the evaluation of the content of what is published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first axis, regarding the form, Murcia and Borba (2008) proposed an evaluation methodology for the scientific journals of accounting and auditing published in English and made available in the CAPES Periodicals Portal. With regard to the evaluation criteria established by CAPES of national and international journals in the areas of Administration and Accounting and Tourism, Oliveira and Martins (2014) emphasize that they are based, mainly, on the evaluation of the form of these journals, without emphasis on the evaluation of the content of what is published.…”
Section: Introductionmentioning
confidence: 99%
“…As already exposed, the evaluation process is an important stage for scientific development (VOLPATO, 2013), being a justification for carrying out this research. Some studies, such as that of Oliveira and Martins (2014) and Martins (2007), have already indicated that there is a need to think about the process of evaluation of research, so that the evaluation problems are mitigated and, therefore, the products achieved are more contributors to scientific development. Thus, the present study will potentially contribute to the improvement of the evaluation process of accounting research journals.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, mesmo não ocorrendo a inativação total das enzimas, o procedimento de branqueamento foi efetivo em reduzir o escurecimento e manter a coloração adequada dos palitos para o processamento nesta cultivar (Figura 3). Em estudo realizado com o branqueamento de cabaça amarga (Nalawade et al, 2018) e batata-doce (Wang et al, 2023) verificou-se que a técnica de infravermelho (IR) requer maior tempo de processamento para a inativação de 90 % da POD, quando comparado com branqueamento e aquecimento por microondas e água quente, resultados semelhantes aos encontrados no presente estudo, onde a POD aumentou com o branqueamento em até 78,5 %.…”
Section: Análise De Pod Ppo L* E B*com Branqueamentounclassified